Reduced Comparison Speed during Visual Search in Late Life Depression - Potter, Guy G. (2013)
Slowed information processing is a prominent deficit in late-life depression (LLD). To better differentiate processing speed components in LLD, we examined characteristics of visual search performance in 32 LLD and 32 control participants. Data showed specific slowing in the comparison stage of visual search in LLD, rather than in encoding/response stages, but also greater overall slowing in LLD during inefficient versus efficient search. We found no group differences on traditional neuropsychological measures of processing speed. Slowed processing speed in LLD may be specific rather than general, which underscores the need to link components of processing speed to underlying neural circuitry.